2021
DOI: 10.1038/s41556-021-00679-w
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical switch regulates the transition towards homeostasis in oesophageal epithelium

Abstract: Epithelial cells rapidly adapt their behaviour in response to increasing tissue demands. However, the processes that finely control these cell decisions remain largely unknown. The postnatal period covering the transition between early tissue expansion and the establishment of adult homeostasis provides a convenient model to explore this question. Here, we demonstrate that the onset of homeostasis in the epithelium of the mouse oesophagus is guided by the progressive build-up of mechanical strain at the organ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 110 publications
0
35
0
Order By: Relevance
“…Other studies have shown that tissue scale properties emerge from cellular scale mechanics in the transition from developing to adult tissues 44 . We have directly addressed this concept in immunologically relevant adult mammalian tissue during homeostasis and immune challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that tissue scale properties emerge from cellular scale mechanics in the transition from developing to adult tissues 44 . We have directly addressed this concept in immunologically relevant adult mammalian tissue during homeostasis and immune challenge.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature in which scRNA-Seq technology is leveraged for molecular characterization of squamous epithelial tissues 27 , 28 , including the normal and diseased esophagus 24 , 29 35 . Our study represents a significant advance in the field of squamous epithelial biology, analyzing the transcriptome of 44,679 esophageal keratinocytes to resolve the cellular landscape of normal murine esophageal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the onset of migration of neural crest cells in Xenopus appears controlled by the stiffening of the underlying mesoderm resulting from axis elongation [16]. An example of a more mature tissue is the epithelium of the ju-venile oesophagus in mice, whose transition from growth to homeostasis is mediated by the mechanotransduction of progressively increasing mechanical strain at the organ level [17].…”
Section: Introductionmentioning
confidence: 99%